Factors associated with pregnancy among unmarried women in Malaysia - Zain, N.M.; Low, W.Y.; Othman, S. (Seameo Regional Tropical Medicine & Public Health, 2015)
Pregnancy among unmarried women may have negative social and health implications in Malaysia. The number of pregnancies among unmarried women has increased in Malaysia, but the socio-demographic profile of these women is unclear. This study aims to evaluate the characteristics of unmarried pregnant women and the factors associated with unmarried pregnancies among young women in Malaysia. We conducted a cross sectional study at six hospitals and six women’s shelters in Peninsular Malaysia during 2011-2012. Unmarried pregnant women were compared with married pregnant women. Participants were interviewed using a structured questionnaire asking for socio-demographic data, family background, risky sexual behavior, social support and pregnancy details. A total of 484 women (239 unmarried and 245 married) were included in the study. Most unmarried subjects were adolescents, from urban areas, from a low socioeconomic group, and lived with parents prior to pregnancy. Age (OR=0.67; 95% CI: 0.61-0.74), studying status (OR=17.33; 95% CI: 2.65-113.19), alcohol use (OR=40.46; 95% CI: 2.51-652.38) exposure to pornographic material (OR=13.48; 95% CI: 3.24-56.01), contraceptive use (OR=0.20; 95% CI: 0.08-0.51), and social support (OR=0.90; 95% CI: 0.86-0.94) were all associated with unmarried pregnancy. These factors need to be considered when designing an intervention program.